2012
DOI: 10.1002/emmm.201200214
|View full text |Cite
|
Sign up to set email alerts
|

Altered γ‐secretase activity in mild cognitive impairment and Alzheimer's disease

Abstract: We investigated why the cerebrospinal fluid (CSF) concentrations of Aβ42 are lower in mild cognitive impairment (MCI) and Alzheimer's disease (AD) patients. Because Aβ38/42 and Aβ40/43 are distinct product/precursor pairs, these four species in the CSF together should faithfully reflect the status of brain γ-secretase activity, and were quantified by specific enzyme-linked immunosorbent assays in the CSF from controls and MCI/AD patients. Decreases in the levels of the precursors, Aβ42 and 43, in MCI/AD CSF te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 31 publications
4
56
1
2
Order By: Relevance
“…Subsequently, they demonstrated that Aβ43 was abundant in vivo , exhibited a greater propensity to aggregate, provoked Aβ42 polymerization, and was more neurotoxic than Aβ42. Recently, Aβ43 was identified and quantified in CSF from human AD/mild cognitive impairment (MCI) patients and control subjects using a commercial Aβ43 enzyme-linked immunosorbent assay (ELISA) [37]. Concentrations in CSF of both Aβ42 and Aβ43 were significantly lower in the patients compared with control subjects indicating an accumulation of these peptides in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they demonstrated that Aβ43 was abundant in vivo , exhibited a greater propensity to aggregate, provoked Aβ42 polymerization, and was more neurotoxic than Aβ42. Recently, Aβ43 was identified and quantified in CSF from human AD/mild cognitive impairment (MCI) patients and control subjects using a commercial Aβ43 enzyme-linked immunosorbent assay (ELISA) [37]. Concentrations in CSF of both Aβ42 and Aβ43 were significantly lower in the patients compared with control subjects indicating an accumulation of these peptides in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…For all brains registered at the bank, written informed consent for their use for medical research was obtained from the patient prior to death or from the patient's family. Brain specimens were collected from Broadmann area 22 (superior temporal gyrus) for 12 AD patients (79.2±4.4 years of age) and 13 control patients (80.4±4.2 years of age) [48]. Detailed descriptions of all subjects, including the relative protein/tubulin ratio for each individual, are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis in our study confirmed that higher levels of PSEN1 in overweight and obese adolescents were due to raised circulating levels of the fulllength protein (Fig 3), but the clinical meaning of this observation is not clear and deserves further studies. Concentrations of PSEN1 have been measured in cerebrospinal fluid 51 and brains from patients with dementia and AD, with inconsistent results. [52][53][54] Phosphorylation of PSEN1 seems to increase the profibrillogenic Ab42/40 ratio and it has been found enhanced in AD brains.…”
Section: Figurementioning
confidence: 99%